THE ROLE OF PARVOVIRUS B19 IN THE DEVELOPMENT OF INFLAMMATORY CARDIOMYOPATHY - A. Yu. Shchedrina; A. A. Skvortsov; K. A. Zykov; A. A. Safiullina; S. N. Tereshchenko (Столичная издательская компания, 2015)
The problem of inflammatory cardiomyopathy is discussed. The etiology, pathogenesis, diagnosis and treatment of inflammatory cardiomyopathy are considered with focus on the role of parvovirus B19.